2023
DOI: 10.1128/spectrum.03357-22
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis of Bacterial Microcompartments and Shell Protein Superstructures by Confocal Microscopy

Abstract: Microcompartments are large, organelle-like structures that help bacteria catabolize targeted metabolites while also protecting the cytosol against highly reactive metabolic intermediates. Their protein shell self-assembles into a polyhedral structure of approximately 100 to 200 nm in diameter.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Alternative morphologies such as sheets of hexamers or arrays of trimeric BMC proteins have been experimentally characterized. Cylinders have been reported in vitro after modifying the ratio of shell components for the Haliangium ochraceum (HO) shell. While the HO shell is quite small, other BMCs, such as carboxysomes, form large icosahedral structures with large triangular planar facets connected together with vertices . The vertices for the icosahedron are filled by pentameric shell proteins, but the approximately planar facets are thought to be a mixture of hexameric and trimeric proteins analogous to the hexameric and trimeric proteins in HO. , In this study, we design a theoretical and computationally feasible mode of the BMC shell protein in sheet conformation and we compare the dynamics and structure of a small periodic BMC sheet model developed in silico to an equivalent shell fragment derived directly from experimental structures .…”
Section: Introductionmentioning
confidence: 89%
“…Alternative morphologies such as sheets of hexamers or arrays of trimeric BMC proteins have been experimentally characterized. Cylinders have been reported in vitro after modifying the ratio of shell components for the Haliangium ochraceum (HO) shell. While the HO shell is quite small, other BMCs, such as carboxysomes, form large icosahedral structures with large triangular planar facets connected together with vertices . The vertices for the icosahedron are filled by pentameric shell proteins, but the approximately planar facets are thought to be a mixture of hexameric and trimeric proteins analogous to the hexameric and trimeric proteins in HO. , In this study, we design a theoretical and computationally feasible mode of the BMC shell protein in sheet conformation and we compare the dynamics and structure of a small periodic BMC sheet model developed in silico to an equivalent shell fragment derived directly from experimental structures .…”
Section: Introductionmentioning
confidence: 89%
“…This has also been found in simulations which assume shell proteins demonstrate no spontaneous curvature of their own [motivated by atomic force microscopy studies on shell subunits ( Sutter et al., 2016 ; Garcia-Alles et al., 2017 )] and can essentially trap a growing cargo droplet out of equilibrium ( Rotskoff and Geissler, 2018 ). This, however, may depend on the system of study as shell proteins have been observed to form sheets, nanotubes, and empty icosahedra among other morphologies, sometimes within the same sample ( Ferlez et al., 2023 ), without the need of cargo templating to induce curvature ( Ferlez et al., 2023 ; Trettel and Winkler, 2023 ; Uddin et al., 2018 ; Hagen AR. et al., 2018 ; Noël et al., 2015 ).…”
Section: Modeling the Physical Principles Underlying Carboxysome Asse...mentioning
confidence: 99%
“…The carbonic anhydrase component in both examples is omitted for clarity. (Ferlez et al, 2023;Trettel and Winkler, 2023;Uddin et al, 2018;Hagen AR. et al, 2018;Noël et al, 2015).…”
Section: The Role Of Shell Components In Bmc Assembly and Morphologymentioning
confidence: 99%